2016
DOI: 10.1002/jeab.194
|View full text |Cite
|
Sign up to set email alerts
|

The Stroop effect at 80: The competition between stimulus control and cognitive control

Abstract: For more than 80 years, researchers have examined the interference between automatic processing of stimuli, such as the meaning of color words, on performance of a controlled-processing task such as naming the color in which words are printed. The Stroop effect and its many variations provide an ideal test platform for examining the competition between stimulus control and cognitive control of attention, as reflected in behavior. The two experiments reported here show that rhesus monkeys, like human adults, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…In any case, the meaning of the stimulus was irrelevant, as the rule was to label the stimulus color. Nevertheless, Lana showed Stroop-like interference from this irrelevant, but highly salient associative cue-as has been reported in thousands of Stroop-task studies with humans 29 Washburn 30,31 reported similar interference effects for a numerical-Stroop task administered to rhesus monkeys (Macaca mulatta) and undergraduate volunteers. This task required rapid judgment of which of two arrays of stimuli contained the most items.…”
Section: Executive Attentionsupporting
confidence: 57%
See 3 more Smart Citations
“…In any case, the meaning of the stimulus was irrelevant, as the rule was to label the stimulus color. Nevertheless, Lana showed Stroop-like interference from this irrelevant, but highly salient associative cue-as has been reported in thousands of Stroop-task studies with humans 29 Washburn 30,31 reported similar interference effects for a numerical-Stroop task administered to rhesus monkeys (Macaca mulatta) and undergraduate volunteers. This task required rapid judgment of which of two arrays of stimuli contained the most items.…”
Section: Executive Attentionsupporting
confidence: 57%
“…Washburn 31 replicated this pattern of results and manipulated the relative demands on the cognitive control of attention, e.g., by varying the ratio of incongruous-to-congruous trials, and by incentivizing fast and accurate responding on incongruous trials. As shown in Figure 1, the monkeys were particularly susceptible to Stroop-like interference, and appeared to be less able than humans to attenuate control by irrelevant, incongruous stimuli on performance, even when motivation was high.…”
Section: Executive Attentionmentioning
confidence: 73%
See 2 more Smart Citations
“…It is due to the ability to direct and focus attention that a choice of a certain activity is made and that mental energy is directed towards it, and due to focusing, which we call enthrallment or concentration in every day speech, that the irrelevant stimuli or distractors are dismissed (Washburn, 2016). The direction and focusing of mental activity on a consciously set goal represents volitional, intentional or active attention.…”
Section: Introductionmentioning
confidence: 99%